Quantification of cyclic twinning-detwinning behavior during low-cycle fatigue of pure magnesium using high energy X-ray diffraction. (August 2019) - Murphy-Leonard, Aeriel D.; Pagan, Darren C.; Beaudoin, Armand; Miller, Matthew P.; Allison, John E.
Highlights: The twin volume fraction doubles in the first five cycles. The compressive stress at which twinning initiate decreases with cycling. The tensile stress at which detwinning is exhausted increases with cycling and is related to the twin volume fraction. With successive cycling, twins persistently form in the same locations (grains) Both EBSD analysis and HEXD confirmed that after a number of cycles residual twins remain in the material. Abstract: The cyclic twinning and detwinning behavior of extruded Mg was investigated using in-situ high energy X-ray diffraction (HEXD) under fully-reversed low cycle fatigue conditions. Measurements were conducted at three levels of applied strain. The initial texture was such that the c-axis in most grains was perpendicular to the loading direction, an orientation in which extension twinning is favored during compressive loading. At strain amplitudes greater than 0.5%, tension-compression asymmetry was observed during cyclic loading and related to cyclic twinning and detwinning. The twinning and detwinning behavior were characterized by monitoring the evolution of X-ray diffraction peaks associated with the basal 0 0 0 2 planes throughout selected cycle. At cyclic strains greater than 0.5%, in-situ HEXD results show that twinning occurs during the compression portion of the cycle and, at early stages of fatigue, most twins are detwinned under reversed loading during the tensile portion of the cycle. It was also observed that as the number of fatigue cycles increases the twin volume fraction increases. After 100–200 fatigue cycles, the detwinning process was observed to be incomplete and a significant fraction of residual twins remained throughout an entire cycle. Using electron back scatter diffraction imaging on the surface of interrupted fatigue tests, twinning and detwinning behavior was investigated and the presence of persistent twins, including residual twins, was observed. At a lower applied strain (0.4%), twinning and tension-compression yield asymmetries associated with twinning were not observed.